Age and anatomical location related hemodynamic changes assessed by 4D flow MRI in the carotid arteries of healthy adults. Issue 128 (July 2020) - Zhang, Guiling; Wang, Zhenxiong; Zhang, Shun; Qin, Yuanyuan; Yao, Yihao; Tang, Xiangyu; Li, Li; Zhou, Yiran; Wu, Di; Chaudhary, Nabin; Liu, Weiyin Vivian; Zhu, Wenzhen
Highlights: 4D flow MRI is an emerging tool to measure hemodynamics and visualize blood changes. Offered suggestion for age and location matched control for carotid artery disease. Choosing proximal ICA and aging as risk factor of atherosclerotic plaque. Implied low volume, velocity, and WSS are more likely to cause atherosclerotic plaques. Abstract: Purpose: To evaluate hemodynamic changes (volume, velocity, wall shear stress, pressure gradient, and energy loss) in the common carotid artery (CCA) and internal carotid artery (ICA) of healthy adults among different ages and anatomical locations using 4D flow MRI. Methods: Sixty-two healthy volunteers aged 20–75 years were enrolled in this study. 4D flow MRI examinations were performed for each subject and were analyzed using the CVI42 platform to generate hemodynamic parameters. Hemodynamic parameters were compared among different age groups and anatomical locations (proximal CCA, distal CCA, proximal ICA and distal CCA) using one-way ANOVA. The paired t -test was used to estimate the differences between left and right vessels. The relationship between age and hemodynamic parameters was quantified by Pearson's correlation coefficient. Results: There were no differences between the left and right carotid arteries for any of the hemodynamic parameters (all p values > 0.05), so we set each vessel as an independent sample. The proximal ICA had significantly lower volume, velocity, wall shear stress, and pressure gradient values than the values determined for other locations ( p < 0.05), and energy loss was similar among different locations. Wall shear stress (except in the distal ICA), velocity, pressure gradient, and energy loss decreased with age ( p < 0.05). Conclusions: The multiparameter analysis of 4D flow MRI can identify age and anatomical location changes in hemodynamic parameters in the carotid arteries of healthy adults. The lower velocity, wall shear stress, and pressure gradient in the proximal ICA and the reduced trend with age may be associated with disease occurrence.